Portlandia season one - Krisel, Jonathan; Fortner, Bryce ca. 20. Jh; Armisen, Fred 1966-; Brownstein, Carrie 1974- (Video Services, 2011)
Contains a series of hilarious character-based shorts all of which take place in 'Portlandia,' where '90s culture reigns supreme and political correctness is all the rage
Orig.: USA 2011
Enth. blooper reel ; extended scenes ; deleted scenes ; Fred Armisen speaks to oes graduates ; thunderant videos ; Fred, Carrie and Jonathan Krisel commentary over all six episodes